Mining metagenomes and metatranscriptomes unveils viruses associated with cutaneous squamous cell carcinoma in hematopoietic stem cell transplant recipients - Jana K. Dickter; Yuqi Zhao; Vishwas Parekh; Huiyan Ma; Badri G. Modi; Wai-Yee Li; Saro H. Armenian; Xiwei Wu; Farah R. Abdulla (Microbiology Spectrum)
ABSTRACT We investigated the presence of viral DNA and RNA in cutaneous squamous cell carcinoma (cSCC) tumor and normal tissues from nine individuals with a history of hematopoietic stem cell transplantation (HCT). Microbiome quantification through DNA and RNA sequencing (RNA-seq) revealed the presence of 18 viruses in both tumor and normal tissues. DNA sequencing (DNA-seq) identified Torque teno virus, Saimiriine herpesvirus 1, Merkel cell polyomavirus, Human parvovirus B19, Human gammaherpesvirus-4, Human herpesvirus-6, and others. RNA-seq revealed additional viruses such as Tobamovirus, Pinus nigra virus, Orthohepadnavirus, Human papillomavirus-5, Human herpesvirus-7, Human gammaherpesvirus-4, Gammaretrovirus, and others. Notably, DNA-seq indicated that tumor samples exhibited low levels of Escherichia virus in three out of nine subjects and elevated levels of Human gammaherpesvirus-4 in one subject, while normal samples frequently contained Gammaretrovirus and occasionally Escherichia virus. A comparative analysis using both DNA- and RNA-seq captured three common viruses: Abelson murine leukemia virus, Murine type C retrovirus, and Human gammaherpesvirus-4. These findings were corroborated by an independent data set, supporting the reliability of the viral detection methods utilized. The study provides insights into the viral landscape in post-HCT patients, emphasizing the need for comprehensive viral monitoring in this vulnerable population.IMPORTANCEThis study is important because it explores the potential role of viruses in the development of cSCC in individuals who have undergone allogeneic HCT. cSCC is common in this population, particularly in those with chronic graft-versus-host disease on long-term immunosuppression. By using advanced metagenomic and metatranscriptomic next-generation sequencing, we aimed to identify viral pathogens present in tumor and adjacent normal tissue. The results could lead to targeted preventive or therapeutic interventions for these high-risk people, potentially improving their outcomes and management of cSCC.